Prognostic value of left and right ventricular strain in heart failure with reduced and preserved ejection fraction: a meta-analysis. (3rd October 2022) - Pastore, M C; Fusini, L; Mandoli, G E; Carrucola, C; Vigna, M; Muratori, M; Pepi, M; Cavigli, L; D'Ascenzi, F; Focardi, M; Valente, S; Mondillo, S; et al.
Abstract: Background: The association of speckle tracking echocardiography measures of left ventricular (LV) and right ventricular (RV) strain with clinical outcome in heart failure with reduced and preserved ejection fraction (HFrEF and HFpEF) has been extensively investigated. In fact, while the contribute of LV ejection fraction (LVEF) for prognosis is controversial, myocardial strain has proven to be a strong and independent prognostic predictor in many HF studies. Purpose: The aim of this meta-analysis was to assess the prognostic value of LV global longitudinal strain (GLS) and free wall RV longitudinal strain (fwRVLS) by 2-dimensional speckle tracking echocardiography in patients with HFrEF, HF with mildly-reduced ejection fraction (HFmrEF) and HFpEF. Methods: A systematic literature search of medical databases including Pubmed, Scopus, Ovid Online, EMBASE, Web of Science, Cochrane Central Register of Controlled Trials, Scopus was performed using PRISMA principles. All relevant studies in English language reporting the predictive value of LV GLS and/or fwRVLS for mortality and/or cardiovascular events in HFrEF, HFmrEF and HFpEF, with follow up >6 months, were identified. Case reports/series and abstract congresses were excluded (Fig. 1). All-cause mortality and a composite endpoint of cardiovascular death, re-hospitalization for HF, cardiac transplantation, ventricular assist device implantation were analyzed. Hazard ratios (HR) were extracted from univariate and multivariate random-effects models reporting on the association of LV GLS and fwRVLS and outcome and described as pooled estimates with 95% confidence intervals (CI). Results: Fifty studies (n=18276 patients) satisfied the inclusion criteria (35 studies in chronic HF, 15 studies in acute HF). Most studies (n=36) included patients with HFrEF, while 14 studies included patients with HFmrEF (n=3) and with HFpEF (n=11); thus HFmrEF and HFpEF were grouped together for the analysis. Overall, 48 studies included LV GLS (median value = −9% [from −17% to −11%], 17 studies included fwRVLS (median value = −18% [from −24% to −14%]). Over a median follow up of 32 [from 7 to 67] months follow up, 5618 (31%) had a cardiovascular event or died. LV GLS and fwRVLS were independently associated with all-cause mortality and the composite outcome, regardless of LVEF (Fig. 2), both in HFrEF (HR 1.26; 95% CI [1.15; 1.37]; p<0.01 for LV GLS and HR 1.06; 95% CI [1.03; 1.09]; p<0.01 for fwRVLS) and in HFpEF (HR 1.07; 95% CI [1.03; 1.12]; p<0.01 for LV GLS and HR 1.08; 95% CI [0.96; 1.21]; p<0.01 for fwRVLS). Conclusions: These meta-analysis data demonstrate that LV and RV strain are associated with mortality and cardiovascular events in patients with HF, HFmrEF and HFpEF and may provide important additive prognostic information. These findings emphasize the potential usefulness of LV GLS and fwRVLS in clinical practice to improve the risk stratification and management of patients with HF regardless of LVEF. Funding Acknowledgement: Type of funding sources: None.